Globalizing academic libraries, vision 2020 : pre-conference volume 2 : the International Conference on Academic Libraries 2009, pt. 2 - International Conference on Academic Libraries 2009 (2009 : University of Delhi); Mitra, Joy.; University of Delhi (New Delhi : Mittal Publications, in association with Delhi University Library System, University of Delhi, 2010)
Papers to be presented at the conference; organized by University of Delhi.
Includes bibliographical references and indexes.
Keywords: Academic libraries -- Congresses; Academic libraries -- Administration -- Congresses; Academic libraries -- Technological innovations -- Congresses